Effects of hemostatic agents on the histomorphologic response of human dental pulp capped with calcium hydroxide - Accorinte, Maria de Lourdes Rodrigues; Loguercio, Alessandro Dourado; Reis, Alessandra; Holland, Robert [UNESP] (My University, 2007)
Objective: To evaluate the response of human pulps capped with a calcium hydroxide [Ca(OH)2] cement after bleeding control with 2 hemostatic agents. Method and Materials: Pulps were exposed on the occlusal floor, and the bleeding was controlled either with saline solution (SS) or 2.5% sodium hypochlorite (NaOCI) (SH). After that, the pulp was capped with Ca(OH) 2 cement and restored with resin composite. After 30 (groups SS30 and SH30) and 60 (groups SS60 and SH60) days, the teeth were extracted and processed with hematoxylin-eosin and categorized in a histologic score system. The data were subjected to Kruskal-Wallis and Mann-Whitney tests (α = .05). Results: Regarding dentin bridge formation, an inferior response of SH60 group was observed when compared to SS60 (P < .05). The response of the SH30 group generally was similar to that of the groups treated with saline solution. However, after 60 days, 2.5% NaOCl showed a trend toward having an inferior response. Conclusion: Using saline solution as a hemostatic agent before pulp capping with Ca(OH)2 resulted in a significantly better histomorphologic response than using 2.5% NaOCl as a hemostatic agent before capping with Ca(OH)2.
Keywords: Biocompatibility; Calcium hydroxide; Hemostatic agents; Human pulp; Pulp therapy; Saline solution; Sodium hypochlorite; calcium hydroxide; hemostatic agent; hypochlorite sodium; sodium chloride; tooth cement; adolescent; adult; chemically induced disorder; drug effect; endodontics; human; oral bleeding; pathology; premolar tooth; pulpitis; secretion; tooth pulp; tooth pulp disease; vascularization; Adolescent; Adult; Bicuspid; Calcium Hydroxide; Dental Cements; Dental Pulp; Dental Pulp Capping; Dental Pulp Necrosis; Dentin, Secondary; Hemostatics; Humans; Oral Hemorrhage; Pulpitis; Sodium Chloride; Sodium Hypochlorite